Civil War barons : the tycoons, entrepreneurs, inventors, and visionaries who forged victory and shaped a nation - Wert, Jeffry D. (Da Capo Press, an imprint of Perseus Books, LLC, a subsidiary of Hachette Book Group, Inc., 2018)
"Before the Civil War, America had undergone a technological revolution that made large-scale industry possible, yet, except for the expanding reach of railroads and telegraph lines, the country remained largely rural, with only pockets of small manufacturing. Then the war came and woke the sleeping giant. The Civil War created a wave of unprecedented industrial growth and development, producing a revolution in new structures, ideas, and inventions that sustained the struggle and reshaped America. Energized by the country's dormant potential and wealth of natural resources, individuals of vision, organizational talent, and capital took advantage of the opportunity war provided. Their innovations sustained Union troops, affected military strategy and tactics, and made the killing fields even deadlier. Individually, these men came to dominate industry and amass great wealth and power; collectively, they helped save the Union and refashion the economic fabric of a nation. Utilizing extensive research in manuscript collections, company records, and contemporary newspapers, historian Jeffry D. Wert casts a revealing light on the individuals most responsible for bringing the United States into the modern age"--